The Virtuous Wehrmacht : Crafting the Myth of the German Soldier on the Eastern Front, 1941-1944 - Harrisville, David A. (Book collections on Project MUSE., 2021)
"This book examines how German soldiers fighting on the Eastern Front during the Second World War rationalized their participation in a criminal campaign, and how the Wehrmacht attempted to assert moral superiority over its Soviet enemies. In the process, it redefines the origins of the myth of the "clean" Wehrmacht"--